2019
DOI: 10.1103/physrevlett.123.243201
|View full text |Cite
|
Sign up to set email alerts
|

Recoil-Induced Asymmetry of Nondipole Molecular Frame Photoelectron Angular Distributions in the Hard X-ray Regime

Abstract: We investigate angular emission distributions of the 1s photoelectrons of N 2 ionized by linearly polarized synchrotron radiation at hν ¼ 40 keV. As expected, nondipole contributions cause a very strong forward-backward asymmetry in the measured emission distributions. In addition, we observe an unexpected asymmetry with respect to the polarization direction, which depends on the direction of the molecular fragmentation. In particular, photoelectrons are predominantly emitted in the direction of the forward ni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…These results on N 2 are gained from the same experimental runs as Refs. [24,25], where further experimental details can be found. Our spectrometer captured ions with 4π collection solid angle, which allowed us to directly obtain the mean value of the momentum from the data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results on N 2 are gained from the same experimental runs as Refs. [24,25], where further experimental details can be found. Our spectrometer captured ions with 4π collection solid angle, which allowed us to directly obtain the mean value of the momentum from the data.…”
mentioning
confidence: 99%
“…Note that in the case of N 2 K-shell photoionization at the high photon energies (E γ ¼ 12-40 keV), Eq. (3) must be extended by even higher-order corrections to properly describe the angle-differential cross section of photoelectrons [24]. There are many misleading formulations on the photon momentum transfer in the literature.…”
mentioning
confidence: 99%
“…These include the translational [1] and rotational Doppler [2] effect in atomic and molecular Auger spectra as well as the rotational recoil [3]. Using a photon energy of 40 keV Kircher et al found that the photoelectron recoil influences the angular distribution of the N 1s photoelectrons of N 2 [4]. Another important field is the investigation of deep double core holes like Ar and Cl 1s −1 2p −1 [5,6] as well as Ne and S 1s −2 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…From these three momentum vectors we calculated the momentum of the N + 2 ion at the instance after photelectron emission. These results on N 2 are gained from the same experimental runs as [22,23], where further experimental details can be found. Our spectrometer captured ions with 4π collection solid angle, which allowed to directly obtain the mean value of the momentum from the data.…”
mentioning
confidence: 99%